Estimating the potential impact of interventions to reduce over‐calling and under‐calling of melanoma. (4th April 2021) - Gibson, M.; Scolyer, R.A.; Soyer, H.P.; Ferguson, P.; McGeechan, K.; Irwig, L.; Bell, K.J.L.
Abstract: Background: Pathologists sometimes disagree over the histopathologic diagnosis of melanoma. 'Over‐calling' and 'under‐calling' of melanoma may harm individuals and healthcare systems. Objectives: To estimate the extent of 'over‐calling' and 'under‐calling' of melanoma for a population undergoing one excision per person and to model the impact of potential solutions. Methods: In this epidemiological modelling study, we undertook simulations using published data on the prevalence and diagnostic accuracy of melanocytic histopathology in the U.S. population. We simulated results for 10 000 patients each undergoing excision of one melanocytic lesion, interpreted by one community pathologist. We repeated the simulation using a hypothetical intervention that improves diagnostic agreement between community pathologist and a specialist dermatopathologist. We then evaluated four scenarios for how melanocytic lesions judged to be neither clearly benign (post‐test probability of melanoma < 5%), nor clearly malignant (post‐test probability of melanoma > 90%) might be handled, before sending for expert dermatopathologist review to decide the final diagnosis. These were (1) no intervention before expert review, (2) formal second community pathologist review, (3) intervention to increase diagnostic agreement and (4) both the intervention and formal second community pathologist review. The main outcomes were the probability of 'over‐calling' and 'under‐calling' melanoma, and number of lesions requiring expert referral for each scenario. Results: For 10 000 individuals undergoing excision of one melanocytic lesion, interpreted by a community pathologist, a hypothetical intervention to improve histopathology agreement reduced the number of benign lesions 'over‐called' as melanoma from 308 to 164 and the number of melanomas 'under‐called' from 289 to 240. If all uncertain diagnoses were sent for expert review, the number of referrals would decrease from 1500 to 737 cases if formal second community pathologist review was used, and to 701 cases if the hypothetical intervention was additionally used. Conclusions: Interventions to improve histopathology agreement may reduce melanoma 'over‐calling' and 'under‐calling'.